The Effect of Broken Home (Household Crisis) on Depression Anxiety Stress Scales (Dass 42) in Students of Sma X Lumajang - NOER KUMALA INDAHSARI; RIZKI AMALIA MEGA FITRIANI (HANG TUAH MEDICAL JOURNAL, 2021)
Abstract: Background : Children or teenagers who are facing Broken homes in their master person directly or indirectly can have an impact on mental health disorders, namely stress, anxiety, and depression, which adversely affect children.  This condition can be said to be a trigger and can make the child moody, sad or long because both parents are divorced. The cause of broken homes is due to several factors, namely: the factor of divorced parents, ugliness, economic period, busy period, and the last is the period of education. Method: This study is a type of observational analytic research with the design of cross-sectional study research and the taking until this research using the method of probability sampling that is random, to find out the level of Broken Home aam this study using a questionnaire made by the research-based on various sources obtained and for stress, anxiety, and depression itself using the questionnaire Depression Anxiety Stress Scale (DASS 42). Result : From the results of the following research can be drawn the doubt that a broken home does not significantly cause high school students in this study to experience stress and anxiety. However, it is known that it can cause depression in high school students in this study significantly. Conclusion: the broken home did not significantly cause high school students to experience stress and anxiety but it can cause depression in high school students is significantly